A cage boron allotrope with high superconductivity at ambient pressure. Issue 26 (16th June 2021) - Liang, Yiwei; Xu, Meiling; Qu, Ziyang; Lin, Shuyi; Hao, Jian; Li, Yinwei
Abstract : A unique B16 cage structure exhibits a T c of 43 K, the highest value among all elemental superconductors at ambient pressure. Abstract : The recent discovery of superconductivity near room temperature in highly compressed superhydrides highlights the key role of the hydrogen cage structure in determining the high superconducting critical temperature. Here, we propose a hitherto unknown metastable cage boron allotrope possessing high superconductivity at ambient pressure. Using first-principles calculations with structure searching, we have predicted various dynamically stable structures for MnB12 that can be possibly synthesized at high pressures and high temperatures. Among these structures the tetragonal t -MnB12 contains unique B16 cages, which are linked to each other to form open channels filled with Mn atoms. The removal of Mn atoms leads to the formation of a tetragonal cage boron allotrope t -B, which possesses partial ionicity due to the slight charge transfer between two inequivalent B atoms. t -B is a potential superconductor with an estimated critical temperature of 43 K, the highest value in elemental superconductors at ambient pressure.